PENGGUNAAN ARTIFICIAL INTELLIGENCE (CHATGPT) TERHADAP EFEKTIVITAS BELAJAR MAHASISWA PPKn FKIP UNIVERSITAS RIAU - Suraya, Dini; Supentri; Erlinda, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing use of artificial intelligence (AI) in higher education, especially ChatGPT, has changed how students participate in educational activities. ChatGPT is an AI-powered application that helps students get information, understand course material, answer academic questions, and do assignments more quickly. Despite these benefits, empirical data is still required to elucidate its impact on students' learning efficacy. Thus, this study looked at how ChatGPT use affected students' learning outcomes in the Civic Education Study Program at Universitas Riau's Faculty of Teacher Training and Education. An explanatory research strategy was used in conjunction with a quantitative method. 141 students were chosen for the research using the Slovin formula with a 5% margin of error. A structured questionnaire was used to collect the data, which IBM SPSS Statistics version 25 was used to analyze using simple linear regression and the Pearson Product Moment correlation test. Students' learning effectiveness and ChatGPT use were shown to be positively and statistically significantly correlated (r = 0.542; p < 0.05). The coefficient of determination (R²) was 0.294, and the regression analysis yielded the equation Ŷ = 25.083 + 0.344X. According to these findings, ChatGPT was responsible for 29.4% of the variance in students' learning efficiency, while factors beyond the purview of this study were responsible for the other 70.6%. Overall, the results show that ChatGPT is a useful use of artificial intelligence in higher education and may promote more effective learning when used carefully, critically, and responsibly.